Konsep Kemahiran Berfikir Aras Tinggi (KBAT) dalam Kurikulum Bersepadu Tahfiz (KBT) - Wan Ali Akbar Wan Abdullah; Nursafra Mohd Zhaffar; Norasmahani Nor; Nor Anisa Musa; Mohd Syaubari Othman (USIM Press, 2024)
Vol. 4 No. 2 (2020)